Visualizations Everywhere: A Multiplatform Infrastructure for Linked Visualizations - Fisher, Danyel; Drucker, Steven; Fernandez, Roland; Ruble, Scott (Transactions on Visualization and Computer Graphics, 2010)
In order to use new visualizations, most toolkits require application developers to rebuild their applications and distribute new versions to users. The WebCharts Framework take a different approach by hosting Javascript from within an application and providing a standard data and events interchange.. In this way, applications can be extended dynamically, with a wide variety of visualizations. We discuss the benefits of this architectural approach, contrast it to existing techniques, and give a variety of examples and extensions of the basic system.